The Effect Of Compensation, Motivation And Discipline Of Work On Employee Performance In Salvatore Ferragamo Book Ciputra World Surabaya PT. TRANSFASHION Indonesia - Triana Mahdani Sidiq; Hermien Tridayanti (Journal of World Conference (JWC), 2020)
Salvatore Ferragamo Cws Boutique has many determinants in developing employee performance, these factors are compensation, motivation and discipline of work. And these factors will be examined statistically which aims to determine how much influence. The variables used are four, namely compensation (X1), motivation (X2), work discipline (X3), and employee performance (Y). Data collection was obtained from distributing questionnaires to all Salvatore Ferragamo Cws Automated Employees. The results show that the variable Compensation (X1), Motivation (X2), and Work Discipline (X3) simultaneously and partially have a significant effect on Employee Performance (Y). This research is a quantitative study with a sample of 30 respondents. The analysis technique used is the path analysis. Based on the results of the study showed that Compensation and Motivation had a significant effect on Employee Performance. However, there are disciplinary variables that are not significant with employee performance.